2014
DOI: 10.1002/j.0022-0337.2014.78.12.tb05842.x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Prosthetic Prescriptions from Dental Students to the Dental Laboratory: Is the Message Getting Through?

Abstract: The aim of this research was to investigate the quality of written prosthetic prescriptions provided by fourth-year dental students to a commercially operated dental laboratory and to ascertain the contribution of interprofessional education to improving prescription quality. Based on guidelines established by the Medicines and Healthcare Products Regulatory Agency of the European Union (Medical Device Directive 93/42/EEC), an audit was conducted prior to and after an educational intervention was delivered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…An audit of Australian dental students’ laboratory work authorizations found that 85% did not meet the required standards. After an intervention with students, however, the number at the next audit dropped to 30% 15 . This is in alignment with other authors who suggest that more emphasis and time be placed on the partnership between dentists and technicians within the dental school curriculum 10,16,20 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…An audit of Australian dental students’ laboratory work authorizations found that 85% did not meet the required standards. After an intervention with students, however, the number at the next audit dropped to 30% 15 . This is in alignment with other authors who suggest that more emphasis and time be placed on the partnership between dentists and technicians within the dental school curriculum 10,16,20 .…”
Section: Discussionsupporting
confidence: 79%
“…These studies have been conducted in many countries and regions, indicating that this is a common, global concern. In the United States, in particular, 2,5,8,12,14 this is likely compounded by many factors, including the large variation in legislation and nomenclature throughout the country 14 and wide variation in educational content concerning laboratory communication and laboratory work authorizations 15–18 . Finally, there has been a decrease in accredited dental laboratory technology education programs and formally trained dental technicians 18 .…”
mentioning
confidence: 99%
“…Most studies have determined the quality of RPD design instructions according to the scores given by technicians as "clear, a guide, poor, none". 1,7,[12][13][14][15][16][17] This kind of scoring may lead the technician to decide in a subjective manner. In the current study, to reduce the subjectivity of the technician, a question about RPD design elements was included.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8,[12][13][14][15][16][17][18][19][20] The studies that investigated the quality of the written prescriptions considered the following items: personal data of the patients, [17][18][19][20] submission and completion date, [16][17][18]20 fee, 20 shade of teeth, [16][17][18][19][20] material selection for prostheses, [16][17][18] design information, 7,8,13,16,17,19,20 and quality of the prescription (assessed as clear, a guide, poor, or none). 1,7,[12][13][14][15][16][17] According to the results of these investigations, the quality of the written prescriptions was often reported as poor 1,7,13,14,…”
mentioning
confidence: 99%
See 1 more Smart Citation